Sifat sensoris minyak atsiri daun kayu manis (cinnamomum burmaniinees ex blume)=Sensory properties of essential oil from Cinnamon leaf (Onnamomum bunnanii Nees ex Blume) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Cinnamon was mainly one of spices used to seasoning ingredient for food processing. Cinnamon was specific aromatic of spices, because from all part can be produced the essential oil, root, bark, leaf and flowers. The objective of this research was to study of the sensory properties from essential oil of cinnamon leaf. The sensories of essential oil, aroma, was evaluated statically using Response Surface Methodology. The optimal result of aroma evaluation from distillation processing were produced at bulk density of 16,802 kilogram/meter cubic, hearing power of 1296,607 watt and the distillation time of 4,784 hour, the condition gave a preference value of aroma 3,551. The validity of application Response Surface Methodology for acceptability of aroma from essential oil was 0,955%.